A PRAGMATIC STUDY OF APOLOGY STRATEGIES IN KURDISH - Othman, Ayad Fayzollah; Ali, Sherzad Sabri (Journal of Duhok University, 2018)
The research entitled “A Pragmatic Study of Apology Strategies in Kurdish  “deals with apology strategies and how to use apology strategies in paradigmatic and syntagmatic relations.It   also   tries   to   determine   ratio  of   using   each   strategy   according   to   general   descriptivemethodology depending on statistics gathered by the researcher. The research has come up with many findings that show the ratio of using each apology strategy in each situation. The present research consists of two chapters and conclusion. The first chapter deals with apology strategies while the second one deal with apology strategies in paradigmatic and syntagmatic relations.